Sistem Informasi Anggaran Pendapatan dan Belanja Desa Berorientasi Objek - Windi Irmayani; Eka Susyatih (Jurnal Khatulistiwa Informatika, 2017)
ABSTRACTThis Object-Oriented Urban Revenue Information System is developed by analyzing the needs of the Village Office of Belitang Satu Kabupaten Sekadau West Kalimantan. The preparation of Revenue and Expenditure Budget still use Microsoft Excel application. To process the data, especially financial data required the use of certain calculation formulas. And the capacity of data in Microsoft Excel is also limited to a certain amount. With the help of Unified Modeling Language (UML), the information system design of Revenue and Expenditure Budget is made. The UML types used are Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Deployment Diagrams. The design of this application can be a reference in making the information system in the future so that it can improve the effectiveness and efficiency of the performance of the  apparatus. Keywords: Information System, Object Oriented and UML.